Short-term exposure to air pollution and mental disorders: a case-crossover study in New York City - Eun-Hye Yoo; John E Roberts; Youngseob Eum; Xiaojiang Li; Lingzhi Chu; Pin Wang; Kai Chen (IOP Publishing, 2022)
There is growing evidence suggesting that exposure to air pollutants is associated with mental disorders. We investigated the impact of short-term exposures to both fine particulate matter (PM _2.5 ) and ozone (O _3 ) assessed at fine spatiotemporal resolutions on emergency room (ER) visits related to mental disorders using 475 755 records from New York City between 2010 and 2016. We assessed the short-term impact of daily air pollution exposure on ER visits using a case-crossover design with conditional logistic regression. We further tested whether the impact of PM _2.5 and O _3 varied by individuals' age, sex, and race/ethnicity, and if associations were modified by the degree of visibility of greenspace at individuals' residences. Results suggested that the relative risk of visiting an ER for mental-disorders increased by 2.78% (95% CI: 1.82%-3.76%) with a 10 $μg\,m^{-3}$ increase in ambient PM _2.5 concentration over a 4 day (d) moving average (lag 0-3 d) and increased by 0.71% (95% CI: 0.28%-1.15%) with a 10 ppb increase in O _3 concentration on a single day lag (lag 1 d), and that these effects were modified by age and race/ethnicity, but not by sex or surrounding greenery. Specifically, we found that age group 19-35 years old and non-Whites were more susceptible to the effects of ambient air pollution exposure. In terms of specific disorders, we found that both PM _2.5 and O _3 have an effect on ER visits for psychotic disorders, but not dementia. Our findings suggest that short-term exposure to ambient air pollution is associated with increased ER visits for mental disorders. Further research is needed to determine the underlying mechanisms by which exposure to PM _2.5 and O _3 is linked to these ER visits.